Analisis Laporan Keuangan dalam Memprediksi Kebangkrutan pada Perusahaan Manufaktur - Sri Fitri Wahyuni (Jurnal Riset Akuntansi, 2019)
The results of research or case studies conducted on plastic manufacturing and packaging companies listing in the 2012-2016 period aim to determine the company's financial condition if it is associated with the possibility of bankruptcy using the Altman Z-Score. One function of financial statement analysis in a company is to determine company life. Prediction of the survival of the company is very important for management and company owners for the survival of the company in anticipating the possibility of potential bankruptcy. The health of a company will reflect the ability to run a business, the distribution of assets, the effectiveness of the use of assets, the results of efforts that have been achieved, obligations that must be repaid and potential bankruptcy to be achieved. In looking at the financial health of the company and predicting the occurrence of bankruptcy, namely by using financial ratios. The ratio used focuses on liquidity ratios, profitability ratios, activity ratios.